AS NOÇÕES DE ACEITABILIDADE/ JUSTIFICABILIDADE NA DESCRIÇÃO DO FUNCIONAMENTO ARGUMENTATIVO DA LINGUAGEM - Zandwais, Ana (Organon, 2002)
This article describes the relation between two different theseson The Theory of Agumentation. The former explains the semantic propertiesof language as responsible for variation of sense within the utterances.The latter deals with variation of sense according to the principleof poliphony.